Fighting for Truth, Justice, and the Asymmetrical Way - Barbara J. Flagg; Katherine Goldwasser (Washington University Law Quarterly, 1998)
For many, symmetry in law enjoys nearly the same status as mom, baseball, and apple pie: it is of the essence of the American way of life. Law would not be law as we know it without the requirement of evenhandedness; justice as we envision her is blindfolded, so as not to see who stands before her. Nevertheless, in the course of our careers (such as they are) in legal academia, the two of us have from time to time proposed the adoption of asymmetrical legal doctrines. We are quite certain that asymmetry is not only tolerable in certain circumstances, but a necessity. Thus we're swimming against the cultural tide, and so have encountered more than a little resistance to our doctrinal proposals. We'd like to take this occasion to explore that resistance and to reflect on its possible sources. In the event that the reader is unfamiliar with the doctrinal recommendations of which we speak, we begin with synopses of them.
Keywords: Critical race theory; Feminist jurisprudence; Equal protection; Legal philosophy; Race discrimination